A case of Degos disease: demonstration of C5b-9-mediated vascular injury. Issue 3 (May 2015) - Umemura, Masayu; Miwa, Yusuke; Yanai, Ryo; Isojima, Sakiko; Tokunaga, Takahiro; Tsukamoto, Hiroyuki; Takahashi, Ryo; Yajima, Nobuyuki; Kasama, Tsuyoshi; Takahashi, Nanako; Sueki, Hirohiko; Yamaguchi, Sayaka; et al.
Abstract A 68-year-old Japanese male presented with atrophic erythematous white lesions with peripheral dark reddish rims on his back. Multiple ulcers were detected from his stomach to his large intestine using endoscopy. Although the patient was given high doses of a steroid, aspirin, dipyridamole, and intravenous immunoglobulin therapy, he died of gastrointestinal hemorrhage, perforation and septic shock. An autopsy examination revealed pauci-inflammatory thrombotic microangiopathy with endothelial cell injury, fibrous occlusive arteriopathy, and vascular C5b-9 deposition in the wall of the gastrointestinal tract from the esophagus to the large intestine as well as in the dermis of the skin.